Medical Crimes in Midwifery Cases: Bibliometrics Analysis - Fitriani N Damayanti; Zulyi Wiyanti; Siti Istiana; Erna Kusumawati; Satriya Pranata (Babcock University Medical Journal)
Background: Medical crimes in midwifery cases, a term used to describe medical crimes during pregnancy, childbirth, and the postpartum period, is a controversial feminist term in global health policy and midwifery practice and research. This work aimed to discover the trend of medical crime publications regarding obstetric cases, the number of citations, and the direction of further research topics.